Kader Posyandu sebagai Agen Pencegahan Primer Tindakan Kekerasan Seksual pada Anak - Anisa Fariani; Ira Paramastri (Faculty of Psychology, Universitas Gadjah Mada, 2015)
This study aimed to examine the effect of child sexual abuse (CSA) prevention training toward the knowledge and examine the effect of health promotion program using lecture and leaflet conducted by cadre applied in community. The method used was a quasi experimental study using the one group pretest-posttest design and untreated control group design with dependent pretest-posttest samples. There were 19 cadres involved in this study. Questionnaires on knowledge, observation, and interview were used in this study. Repeated measures anova and mixed anova were used to analyse the quantitative data, descriptive analyse was used to analyse data from observation and interview. Data analyse was used to identify differences of knowledge before-after CSA prevention training and to examine the effect of lecture and leaflet toward improvement of community knowledge. The results showed there was a significant difference in knowledge before and after training (F=20.245, p<0.05). Lecture and leaflet was effective to increase knowledge about CSA (F=3.379, p<0.05). Leafletwas more effective to increase knowledge (MD=-2.824; p<0.01) than lecture (MD=-2.355; p<0.01).